Prevalence and intensity of intestinal and soil-transmitted helminths infection among children in internally displaced camps in Mogadishu Somalia - Bashiru Garba; Hodo Aideed Asowe; Najib Isse Dirie; Yushau Umar; Abdikani Omar Salah; Ahmed Abdirahim Hussien; Ikram Abdirahman Mohamud Alasow; Fartun Abdullahi Hassan Orey; Jihaan Hassan; Jamal Hassan Mohamoud; Mohamed Hussein Adam; Mohamed Adam Mahamud; et al. (Scientific Reports)
Abstract Intestinal and soil-transmitted helminth (STH) infections are significant public health concerns in Somalia and are driven by poor sanitation, contaminated water, and inadequate hygiene practices. This study was undertaken to assess the prevalence and intensity of intestinal and soil-transmitted helminth infections among school-aged children in the Deyniile and Kahda internally displaced persons camps. A well-structured questionnaire was used to collect sociodemographic, behavioral and environmental data from the respondents, while fresh stool samples were collected to detect helminths via the cellophane-based Kato–Katz technique. Bivariate and multivariate logistic regression analyses were used to measure the strength of the associations. The overall prevalence of intestinal and soil-transmitted helminth infection was 72.5% (232/320). A mixed effects logistic regression analysis revealed that fathers with secondary school education (P = 0.039; AOR = 0.148; 95% CI 0.024–0.904) and children living in Kahda (P = 0.033; AOR = 0.519; 95% CI 0.283–0.950) had a significantly lower risk of helminths infection. The prevalence of helminths in both vamps was high. Dirty fingernails (P = 0.462; AOR = 0.72; 95% CI 0.30–1.73), eating unwashed fruits (P = 0.654; AOR = 0.86; 95% CI 0.45–1.66) and walking barefoot (P = 0.803; AOR = 1.13; 95% CI 0.43–2.96) were all not associated with increased risk of infection, including sanitary condition at home (P = 0.054; AOR = 2.99; 95% CI 0.98–9.17).